2023
DOI: 10.1136/jcp-2022-208615
|View full text |Cite
|
Sign up to set email alerts
|

Circulating IL-6 is associated with disease progression in BRAFwt metastatic melanoma patients receiving anti-PD-1 therapy

Abstract: AimsDespite efficacy of anti-PD-1 blockade in treatment of metastatic melanoma (MM), many patients achieve rapid disease progression (DP). Therefore, the aim of this study is to better define biomarkers for DP by analysing levels of circulating cytokines TGF-β, IFN-γ, IL-6, IL-8 and IL-10 in MM patients prior to anti-PD-1 therapy.MethodsCytokine levels were evaluated before therapy with pembrolizumab in peripheral blood of BRAF wild-type (wt) MM patients by ELISA method.ResultsIn this study, we give pretherapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 39 publications
(47 reference statements)
0
11
0
Order By: Relevance
“…High serum IL‐6 level was predictive of poor efficacy and short PFS in patients with non‐small‐cell lung cancer, and decrease in IL‐6 was associated with anti‐PD‐1 responses 25,26 . Moreover, IL‐6 level was correlated to early disease progression in melanoma patients receiving anti‐PD‐1 therapy 27 . To our knowledge, the prognostic variables in cHL treated with PD‐1 blockade therapy have not been clearly examined.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…High serum IL‐6 level was predictive of poor efficacy and short PFS in patients with non‐small‐cell lung cancer, and decrease in IL‐6 was associated with anti‐PD‐1 responses 25,26 . Moreover, IL‐6 level was correlated to early disease progression in melanoma patients receiving anti‐PD‐1 therapy 27 . To our knowledge, the prognostic variables in cHL treated with PD‐1 blockade therapy have not been clearly examined.…”
Section: Discussionmentioning
confidence: 96%
“…25,26 Moreover, IL-6 level was correlated to early disease progression in melanoma patients receiving anti-PD-1 therapy. 27 To our knowledge, the prognostic variables in cHL treated with PD-1 blockade therapy have not been clearly examined. In this study, we reported the significance of serum baseline IL-6 for cHL patients to predict remission duration of anti-PD-1-combined immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the IL-6-induced HDAC6 not only upregulated the IL-6 downstream JAK2/STAT3 pathway but also co-activated TGF-β/Smad3 signaling [ 121 ]. The increased level of circulating IL-6 has been related to metastatic disease and poor prognostic outcome in cancer patients with diverse histological tumor types, as reported in numerous studies [ 122 , 123 , 124 ].…”
Section: Roles Of Hdac6 In Physiological Processesmentioning
confidence: 99%
“…Since IL‐6 can be utilized as an indicator for predicting the efficacy of anti‐PD‐1 therapy, the potential correlation between these factors was further explored. The association is also between high IL‐6 with negative effects of therapy in other tumors 30 …”
Section: Introductionmentioning
confidence: 98%
“…The association is also between high IL-6 with negative effects of therapy in other tumors. 30 The associations of particular serum blood biomarkers used in routine clinical practice with treatment response and PFS of patients with advanced NSCLC on anti-PD-1 therapy were investigated, with the aim of identifying available biomarkers that could aid in predicting treatment responses or PFS with clinical applicability. Our results suggest that the D-dimer and IL-6 have significant value in predicting response to anti-PD-1 therapy.…”
Section: Introductionmentioning
confidence: 99%